The legal forms of establishing payment and accumulative monetary functions - Proskurina , K.Yu. (Bulletin of the Karaganda University “Law Series”, 2021)
The subject of this scientific research is the legal forms of establishing payment and accumulative monetary functions. At the present stage of the development of legal regulation of the monetary system of the Republic of Kazakhstan, the payment monetary function is, in comparison with other economic monetary functions, more comprehensively reflected in the legislation of the Republic of Kazakhstan. The legal forms of establishing accumulative monetary function in the current legislation, on the contrary, can be found “between the lines”, or are indirectly fixed, which necessitates their special search and interpretation. The author of this work provides not only the author’s definitions of the proposed terms, but also established the difference in such concepts important for the modern economy as “means of payment”, “legal means of payment”, “the only legal means of payment” and “illegal means of payment”. In light of the emergence and introduction of “private” (non-state) money into the market economy, the emergence of cryptocurrencies and the need to de[1]termine their legal status, the establishment of such a theoretical distinction seems to be very relevant. Based on the results of the study, conclusions were drawn and recommendations for improving the current legisla[1]tion were given. The methodology of this scientific work was made up of analytical, systemic, comparative, formal legal methods. Among other things, the theoretical basis of the study includes the works of scientists in the field of financial and civil law of both the Republic of Kazakhstan and the Russian Federation. Taking into account that money is an economic and legal category, the author also studied and applied the works of economists. The results, obtained in the course of this research can be used in writing scientific and practical works in this area of law, systemic interpretation of the rules of law governing commodity-money relations, as well as for the purpose of improving the current legislation of the Republic of Kazakhstan.